Increased serum sialic acid is associated with morbidity and mortality in a murine model of dengue disease. (17th September 2019) - Espinosa, Diego A.; Beatty, P. Robert; Puerta-Guardo, Henry; Islam, M. Nurul; Belisle, John T.; Perera, Rushika; Harris, Eva
Abstract : Dengue virus (DENV) causes the most prevalent arboviral infection of humans, resulting in a spectrum of outcomes, ranging from asymptomatic infection to dengue fever to severe dengue characterized by vascular leakage and shock. Previously, we determined that DENV nonstructural protein 1 (NS1) induces endothelial hyperpermeability, disrupts the endothelial glycocalyx layer (EGL) in vitro and triggers shedding of structural components, including sialic acid (Sia) and heparan sulfate. Here, using a murine model of dengue disease disease, we found high levels of Sia and NS1 circulating in mice with DENV-induced morbidity and lethal DENV infection. Further, we developed a liquid chromatography/mass spectrometry-based method for quantifying free Sia in serum and determined that the levels of free N-glycolylneuraminic acid were significantly higher in DENV-infected mice than in uninfected controls. These data provide additional evidence that DENV infection disrupts EGL components in vivo and warrant further research assessing Sia as a biomarker of severe dengue disease.